Changes in the Structural Dimensionality of Selenidostannates in Ionic Liquids: Formation, Structures, Stability, and Photoconductivity. Issue 27 (15th May 2013) - Lin, Yumei; Xie, Dewang; Massa, Werner; Mayrhofer, Leonhard; Lippert, Sina; Ewers, Benjamin; Chernikov, Alexey; Koch, Martin; Dehnen, Stefanie
Abstract In situ transformations of selenidostannate frameworks in ionic liquids (ILs) were initiated by treatment of the starting phase K2[Sn2Se5] and the consecutive reaction products by means of temperature increase and/or amine addition. Along the reaction pathway, the framework dimensionalities of the five involved selenidostannate anions develop from 3D to 1D and back, both in top‐down and bottom‐up style. Addition of ethane‐1, 2‐diamine (en) led to the reversion of the 2D→1D step from 2D‐{[Sn24Se56]16−} to 1D‐{[Sn6Se14]4−}. As rationalized by DFT investigations, the 2D anion is thermodynamically favored. Photoconductivity measurements reveal that all samples show Schottky contact behavior with absolute thresholds below 10 V. One of the samples exhibits conductive states within the energy range of visible photons.